A Study on Estimating the Parameter of the Truncated Geometric Distribution. Issue 3 (3rd July 2022) - Park, Chanseok; Gou, Kun; Wang, Min
Abstract: We consider the truncated geometric distribution and analyze the condition under which a nontrivial maximum likelihood (ML) estimator of the parameter p exists. Additionally, the uniqueness criterion of such an ML estimator is also investigated. Our results indicate that in order to ensure the existence of a nontrivial ML estimator, the sample mean should be smaller than the midpoint of the two boundary positions. Without such a condition, the ML estimator will only exist trivially at p  = 0. Finally, we demonstrate that the same condition is also required for the existence of the method of moments estimator. Our results lead to a rigorous understanding of the two estimators and aid in the interpretation of experimental designs that incorporate the truncated geometric distribution.